Achieving Sustainable Procurement in Construction Projects: The Pivotal Role of a Project Management Office (Construction Economics and Building, 2021)
Environmental and ecological impacts associated with construction activities have become an ever-increasing concern, especially the considerable amount of waste generated on construction sites. Regulations and growing client pressure on meeting environmental standards have led contractors to adopt sustainable practices and try to embed this concept in their processes. Sustainable procurement management (SPM) as a potential solution takes the environmental consequences of procurement decisions into account and integrates sustainable practices into project procurement to bring positive environmental outcomes. Previous research has mainly focused on the public sector in achieving green procurement, yet this study attempts to highlight internal capacities that help private organisations manage the requirements associated with practicing sustainability. It is theorised that robust management structures, specifically project management offices (PMOs), would enhance the oversight capabilities of contractors in implementing the SPM process. The objectives of the current study are to (1) identify the requirements of a sustainable project procurement process in construction sites based on a literature review, and (2) explore the facilitative role of PMO units in achieving these requirements in the private sector. A literature review was conducted followed by a qualitative survey to solicit the viewpoints of construction professionals in principle contracting firms. As a result of the study, we identified 17 sustainability requirements and found that PMOs boost collaboration and improve the quality of decision making towards sustainable procurement. The findings (1) explain how PMOs support sustainability, (2) provide insights on implementing sustainable practices in project purchases, and (3) improve theoretical understanding of the SPM principles.